MARKETING STRATEGY OF MUDHARABAH SAVINGS (TABAH) TO INCREASE CUSTOMERS AT BMT NU EAST JAVA - Mohammadjavad Mahdavinejad (Universitas Nurul Jadid, 2023)
Competition between conventional and sharia financial institutions makes people cautious in choosing, due to a perception that conventional services are better. Customer satisfaction is a benchmark for institutional progress, with savings as the main instrument for recruiting public funds and raising capital. This research aims to explore the role of BMT NU Mayang Branch, Jember Regency in marketing mudharabah savings products as a sharia financial option. It focuses on two aspects: identifying the marketing strategies implemented by BMT NU Mayang Branch in promoting mudharabah savings products and evaluating factors that support or hinder marketing efforts at BMT NU Mayang Branch.The research method is qualitative with a descriptive approach, aimed at describing and explaining subjects, classifying them, and drawing conclusions. These conclusions facilitate observations and further research. Data collection techniques include observation, interviews, and documentation.Theories used in this research are marketing, economics, communication, and management theories. The results are: 1) BMT NU Mayang Jember Branch markets mudharabah savings products and increases the number of customers through effective marketing strategies such as cooperation, maximum service, digital promotions, and word of mouth. 2) Marketing obstacles include a lack of interaction skills and trust in BMT NU, but supportive economic conditions and effective social media use are significant supporting factors.Strategies used at BMT include word of mouth, door-to-door, focus on main targets, and digital promotions. Door-to-door is the most prominent strategy, involving savings officers visiting customers' homes to collect savings or provide loans.